5 x × 5 x × 3 x − 1 × 3 2 x = 1 2 5 x × 3 2 x × 3 2 x
If x satisfy the equation above, find 3 ( 1 5 x ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The first line of your solution has an extra × 5
5 x × 5 x × 3 x − 1 × 3 2 x 5 x + x 3 x − 1 + 2 x 5 2 x 3 3 x − 1 5 2 x − 2 x 3 3 x − 1 − 3 x + 1 5 0 3 0 ⇒ 3 ( 3 x ) ( 5 x ) 3 ( 3 × 5 ) x ⇒ 3 ( 1 5 x ) = 1 2 5 x × 3 2 x × 3 2 x = ( 5 3 ) x 3 2 x + 2 x = 5 3 x 3 4 x = 5 3 x − 2 x 3 4 x − 3 x + 1 = 5 x 3 x + 1 = 1 = 1 = 1
Just by knowing a m • a n = a m + n a m • b m = ( a b ) m Anyone can do it!!
5 x × 5 x × 3 x − 1 × 3 2 x = 1 2 5 x × 3 2 x × 3 2 x
5 x + x × 3 x − 1 + 2 x = ( 5 3 ) x × 3 2 x + 2 x
5 2 x × 3 3 x − 1 = 5 3 x × 3 4 x
1 = 5 2 x × 3 3 x − 1 5 3 x × 3 4 x
1 = 5 3 x − 2 x × 3 4 x − ( 3 x − 1 )
1 = 5 x × 3 x + 1
1 = 5 x × 3 1 × 3 x
1 = 3 ( 1 5 x )
Problem Loading...
Note Loading...
Set Loading...
Solution w/ quite detail explanation
5 x × 5 x × 3 x − 1 × 3 2 x = 1 2 5 x × 3 2 x × 3 2 x
Rewrite the equation by simplifying it. (optional)
5 2 x × 3 x − 1 × 3 2 x = 5 3 x × 3 2 x × 3 2 x
Divide both sides by 3 2 x since both sides have the factor of it.
5 2 x × 3 x − 1 = 5 3 x × 3 2 x
Divide 5 2 x and 3 2 x both sides.
3 2 x 3 x − 1 = 5 2 x 5 3 x
Now simplify both sides.
3 x − 1 − 2 x = 5 3 x − 2 x
3 − x − 1 = 5 x
3 − x − 1 can actually be written as 3 − x × 3 1
Therefore,
3 − x × 3 − 1 = 5 x
Divide 3 − x both sides to get 1 5 x
3 − 1 = 3 − x 5 x
3 1 = 3 x 1 5 x
Note that 3 − 1 can be written as 3 1
3 1 = 5 x × 3 x
1 5 x = 3 1
Hence,
3 ( 1 5 x ) = 3 ( 3 1 )
3 ( 1 5 x ) = 1